British Scholar’s Perceptions on Capitalism and Religious Ethics In The Age of Techno-Feudalism - Abdurrahman Mas'ud; Nur Said; Sus Eko Zuhri Ernada (Indonesian Journal of Islamic Literature and Muslim Society, 2024)
In a feudal system, land is the main source of wealth and power. Meanwhile, Techno-Feudalism holds the concentration of power and data wealth in the digital realm which has a significant impact on economic, social and political structures. This research discusses the dialectics of religious ethics, capitalism and Indonesian citizenship in the face of the rise of techno-feudalism from the perspective of British scholars' orientalism. This study uses a multi-faceted approach, combining interviews, content analysis and scientific publication studies to reveal the complex layers of how British intellectuals interpreted and engaged with the historical discourse of inter-religious interaction in Indonesia amidst the shift from feudalism to techno-feudalism. The challenges of Indonesian citizenship in global civility and the flow of capitalism are the center of attention in this research. This research shows that the complexity inherent in cross-cultural academic interactions demands the growth of different perspectives on citizenship and national identity amidst the rise of techno-feudalism that has taken over capitalism. In this position, the power of religious ethics is increasingly relevant, being put forward as a controlling force towards moderate citizenship and economic system. As a recommendation that techno-Feudalism holds the concentration of power and wealth in the digital realm, which in many ways is considered potentially dangerous, must be immediately addressed in the necessary ways to explore and depict a better future.